Achados do paleolítico inferior e médio da região de Rio Maior - Cardoso, João Luís (2017)
A study of Iithic material collected on different occasions from Tertiary and Quaternary deposits in the area of Rio Maior (Santarém). The quality and homogeneity of these artifacts are almost an exception in the Portuguese Lower and Middle Paleolithic. The identification in situ of some of these findings allows for a more accurate chronology of the deposits.